Membrane proteins specified by herpes simplex viruses. I. Identification of four glycoprotein precursors and their products in type 1-infected cells. - Spear, P G (1976)
Polypeptide precursors to the major glycoproteins specified by herpes simplex virus type 1 were identified in immunoprecipitation experiments using antisera that reacted specifically with the viral glycoproteins and their precursors. The results demonstrate that the major glycosylated proteins detected in infected cells are derived from four antigenically distinct polypeptides. Three of these polypeptides become glycosylated in two discrete stages, yielding partially glycosylated intermediates and fully glycosylated products. The final products are the predominant species detected in cytoplasmic virions and in plasma membranes. The fourth polypeptide precursor appears to acquire very little carbohydrate and differs in several respects from the other three precursors.